Bending performance analysis of precast composite beams with precast ECC plate. (October 2021) - Cui, Tao; HE, Haoxiang; Zhao, Xinli; Zhou, Daxing
Abstract: Despite the popularity of precast concrete (PC) composite beams in urban construction, some shortcomings still exist in application. These include easy cracking, poor deformation ability, susceptibility to impact damage. To solve the above problems, engineered cementitious composites (ECC) are applied in the tension zone of PC beam specimens to improve the mechanical properties. Eleven specimens are designed and loaded. An analysis of the bending behavior is presented considering the effects of the precast ECC plate thickness, reinforcement connection mode, and reinforcement ratio on the bending performance. The mechanical characteristics of each stage are analyzed in detail. The crack width development trend is measured. Results show that the bearing capacity and ductility of the PC beams with precast ECC plates and post-pouring zones are higher than those of reinforced concrete (RC) beams; The calculation method given in this paper can reflect the mechanical performance well. The reinforcement stress can be effectively transmitted by a sleeve or hoop connection; the precast ECC plate can effectively control the crack width. The PC beam with ECC baseplate and post pouring area presented in this paper has good mechanical performance and is suitable for engineering construction.